Management of Higher Education in Ukrainian SSR in Conditions of Strengthening the Repressive Totalitarian System (Late 1920s – Early 1930s) - Mazurenok, Maryna (Pedagogical Discourse, 2017)
At the present stage our society needs reforms in all spheres of life. Search of the best ways to build the educational process in higher education is not possible without the historical lessons of the past. Only the experience of previous generations, it is necessary to develop the education system today. Therefore, special importance is the study of the People’s Commissariat of Ukrainian SSR in terms of abolition of democratization in education, the emergence of the totalitarian system. The article highlights the main activities of the People’s Commissariat of Education of the Ukrainian SSR on the reorganization of higher education in the late 1920s - early 1930s. The legislative framework of the process of unification of Ukrainian higher education in the Russian sample has been analysed. The views of the USSR the People’s Commissariat for reform of higher education have been revealed. The features of the educational process, universities definite period have been described. Much attention has been paid to the formation of the contingent of university students, social reforms in academic institutes and colleges, strengthening of administrative influence on Ukrainian students, the politicization of student societies and organizations. The impact of government policies on the development of higher education of USSR, including the increasingly repressive and totalitarian regime has been traced. It was found that period during the late 1920’s - early 1930’s. is characterized by consolidation of administrative-command system, the formation of the personality cult of Stalin, the spread of communist ideas. Stalinist repression caused significant losses in the education system of Ukraine. This led to a gradual strengthening in the educational process of universities repetitive forms and universal methods of training and education, use them without opportunities, needs and interests of students. Key words: People’s Commissariat of Ukrainian SSR, reorganization, unification, high educational establishments, students.